Characteristics and Effects of Multiple and Mixed Funding Flows to Public Healthcare Facilities on Financing Outcomes: A Case Study From Nigeria - Onwujekwe, Obinna; Mbachu, Chinyere; Ezenwaka, Uche; Arize, Ifeyinwa; Ezumah, Nkoli (Frontiers in Public Health, 2020)
Most public hospitals in Nigeria are financed by funding flows from different health financing mechanisms, which could trigger different provider behaviours that can affect the health system goals of efficiency, equity and quality of care. The study examined how healthcare providers respond to multiple funding flows (MFF) and the implications of such flows for achieving equity, efficiency and quality. A qualitative study of healthcare providers and purchasers in Enugu state, Nigeria was used. Key informants were individual healthcare providers and decision makers in hospitals, Ministry of Health, National Health Insurance Scheme and Health Maintenance Organizations. Service users were purposively selected for focus group discussions (FGDs). A total of 66 key informant interviews and 8 FGDs were conducted. Findings: The MFF that were received by public hospitals varied by type of health facility (Secondary vs. Tertiary), ownership of health facility (Federal government vs. State government) and population served. Out-of-pocket payment (OOP) and government budget were the only recurring forms of funding to all the public hospitals. It was found that MFF lead to predictability and stability of funding to public hospitals. It increased their financial pool and capacity to undertake capital projects, and enabled provision of wider range of services to clients. They also gave a sense of security to health facilities, because there would always be a back-up source of funding if one flow delays or defaults in payment. Nevertheless, health providers were seen to shift resources from less attractive to more attractive flows in response to relative size, and perceived adequacy, predictability and flexibility of funding flow. Patients were also shifted from less predictable to more predictable funding flows and providers charged different rates to different funding flows to make up for inadequacies in some sources of funding. The negative consequences of MFF led to inefficiency in use of resources, differential quality of care and inequities in resource distribution and access to services. In some instances, there were better quality of care for clients and improved access to services. Conclusion: MFF to public hospitals are beneficial as well as constraining to health providers, which affect health systems goals.